2023
DOI: 10.1109/tnse.2022.3191601
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain and Deep Learning for Secure Communication in Digital Twin Empowered Industrial IoT Network

Abstract: The rapid expansion of the Industrial Internet of Things (IIoT) necessitates the digitization of industrial processes in order to increase network efficiency. The integration of Digital Twin (DT) with IIoT digitizes physical objects into virtual representations to improve data analytics performance. Nevertheless, DT empowered IIoT generates a massive amount of data that is mostly sent to the cloud or edge servers for real-time analysis. However, unreliable public communication channels and lack of trust among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…To improve consensus efficiency, a novel DT-DPoS (digital twin delegated proof of stake) consensus protocol is also designed to better suit the digital twin-enabled ITS scenarios. Several research efforts have been reported in the literature to secure and optimize digital twin-based applications such as industrial metaverse [60], [61], vehicular traffic management [62], maritime transportation systems [7], industrial IoT [63], edge offloading [64]- [66], and virtual reality (VR) [67].…”
Section: Security and Privacy Countermeasures In Iodt A Iodt Data Sec...mentioning
confidence: 99%
“…To improve consensus efficiency, a novel DT-DPoS (digital twin delegated proof of stake) consensus protocol is also designed to better suit the digital twin-enabled ITS scenarios. Several research efforts have been reported in the literature to secure and optimize digital twin-based applications such as industrial metaverse [60], [61], vehicular traffic management [62], maritime transportation systems [7], industrial IoT [63], edge offloading [64]- [66], and virtual reality (VR) [67].…”
Section: Security and Privacy Countermeasures In Iodt A Iodt Data Sec...mentioning
confidence: 99%
“…To improve consensus efficiency, a novel DT-DPoS (digital twin delegated proof of stake) consensus protocol is also designed to better suit the digital twin-enabled ITS scenarios. Several research efforts have been reported in the literature to secure and optimize digital twin-based applications such as industrial metaverse [60], [61], vehicular traffic management [62], maritime transportation systems [7], industrial IoT [63], edge offloading [64]- [66], and virtual reality (VR) [67].…”
Section: Security and Privacy Countermeasures In Iodt A Iodt Data Sec...mentioning
confidence: 99%
“…Digital twin-enabled industrial IoT usually relies on cloud/edge servers for compute-intensive and real-time data processing. Aimed to mitigate the unreliable public communication channels and build trust among participating entities, Kumar et al [63] integrate deep learning and blockchain to deliver decentralized data learning and digital twin services in industrial IoT. The smart contracts are deployed atop the blockchain platform to guarantee data integrity and authenticity, and an intrusion detection system (IDS) is built based on long short term memory (LSTM), sparse autoencoding (SAE), and multi-head self-attention (MHSA) techniques to make sure the information obtained from the blockchain is accurate.…”
Section: Security and Privacy Countermeasures In Iodt A Iodt Data Sec...mentioning
confidence: 99%
“…In addition, from the function perspective, the attribute-based signature primitive could be combined with some blockchain-based solutions [41][42][43][44] to realize fine-grained access control and enhanced privacy preservation for the blockchain environment. Table 1.…”
Section: Attribute-based Signaturementioning
confidence: 99%